2008
DOI: 10.1007/s00299-008-0548-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compound localisation in Polypodium vulgare L. rhizomes after mannitol-induced dehydration and controlled desiccation

Abstract: Polypodium vulgare L. is a desiccation-tolerant fern that can withstand successive dry periods in its life cycle. To better understand this mechanism, the current study was undertaken to assess the role of phenolic compounds in rhizome dehydration and determine their localisation in the rhizome cells after enforced dehydration in mannitol solution or controlled desiccation with or without abscisic acid (ABA) pretreatment. Phenolic distribution at the subcellular level was studied using gold particle-complexed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
2
6
0
1
Order By: Relevance
“…Few plastids were labeled, only those containing starch grains were marked with some gold granules, and the gold granules gathered around the starch grains or directly on the starch grains. These results were consistent with the immune gold labeling results of polyphenols in rhizome of Polypodium vulgare L. studied by [23]. As to the partial labeling of the starch grains, its reason is not yet clear.…”
Section: Synthesis and Transfer Of The Phenolic Compoundssupporting
confidence: 81%
See 1 more Smart Citation
“…Few plastids were labeled, only those containing starch grains were marked with some gold granules, and the gold granules gathered around the starch grains or directly on the starch grains. These results were consistent with the immune gold labeling results of polyphenols in rhizome of Polypodium vulgare L. studied by [23]. As to the partial labeling of the starch grains, its reason is not yet clear.…”
Section: Synthesis and Transfer Of The Phenolic Compoundssupporting
confidence: 81%
“…Some black flocculent substance was found on the cell wall, but only at sites surrounding large intercellular space. Because lipids in the cell are also osmiophilic, it is difficult to differentiate them from the phenolic compounds, but immunocytological localization techniques revealed that cell wall was the distribution sites of phenolic compounds [16,23]. Therefore, laccase-colloidal gold labeling was used to locate the phenolic compounds in the cells.…”
Section: Synthesis and Storage Sites Of Phenolic Compoundsmentioning
confidence: 99%
“…These observations led us to speculate that the degradation product of starch grains in the chloroplasts may provide an important precursor for CGA synthesis and that the reduced abundance of laccase-gold particles around the starch grains later might be explained (at least partially) by transfer of CGA into vacuoles for storage at the later stages. Consistent with this notion, previous studies have shown that phenolic acids in Polypodium vulgare L. rhizomes were mainly distributed around the amyloplast starch grains 51 and that starch in the chloroplasts was involved in the synthesis of tannins or phenolic acids 5254 . In addition, our cellular evidence also suggests that CGA synthesized in the cytoplasm migrated into the large central vacuoles mainly through the aggregation of vesicles and then fusion of the vesicular membranes with the vacuolar membranes.…”
Section: Discussionsupporting
confidence: 64%
“…6B) similar to observations in soybean roots (Szafrańska et al, 2005). The predominant vacuolar localization of PhC, as revealed by TEM, was reported by many authors in different plant species (Kuraś et al, 1999;Szafrańska et al, 2005;Bagniewska-Zadworna et al, 2008;Glińska et al, 2009). The chemical character of PhC visualized with OsO 4 remains unknown.…”
Section: Phc Localizationmentioning
confidence: 76%